Judicial Ethics and Court Integrity: A Reflection on Cases of Ethical Violations (Indonesian Court and Justice Review, 2024)
Judicial ethics and court integrity are critical components of a fair and just legal system, yet instances of ethical violations in the judiciary pose serious challenges to public trust and the overall credibility of legal institutions. This research delves into the nature and impact of ethical misconduct within the judiciary, focusing on specific cases where judicial actions have breached ethical standards. By analyzing a variety of documented violations, ranging from conflicts of interest to biases and corruption, this study aims to uncover the underlying causes of these ethical lapses. Through qualitative methods, including case study analysis and interviews with legal practitioners, the research highlights how such violations not only harm individual cases but also erode public confidence in the impartiality of the courts. The findings indicate that systemic issues, such as insufficient oversight, lack of accountability, and cultural factors within the legal profession, contribute significantly to ethical misconduct. This study's novelty lies in its interdisciplinary approach, combining legal analysis with insights into institutional culture and human behavior. As the demand for judicial reform intensifies globally, addressing these ethical challenges has become urgent. This research offers valuable perspectives on how to strengthen ethical standards, improve transparency, and establish more effective mechanisms for judicial oversight. Ultimately, it contributes to both national and international conversations about ensuring that courts remain paragons of integrity and fairness.